Email Information Flow in Large-Scale Enterprises - Karagiannis, Thomas; Vojnovic, Milan (2008)
We present analysis results of email communications in a large-scale enterprise network. Our study first focuses on understanding the social graph induced by email communications between individual users. Specifically, we examine how email communication flows are correlated with user profiles, the organization structure, and how outside information penetrates the enterprise. We then concentrate on understanding the information processing load imposed to users and the strategies applied by users in email triage. To the best of our knowledge, this is the first measurement study of email communications of a global enterprise network comprising email data from over 100,000 employees spread across multiple continents. Our analysis results inform the design of network applications that takes into account typical user behaviour in social interactions and solitary information processing. Our large-scale dataset further allows us to examine the validity of several hypotheses suggested by the social network theory.